Case report: dose-dependent interaction between dexamethasone and voriconazole in severely ill patients with non-Hodgkin’s lymphoma being treated for invasive pulmonary aspergillosis - Huang, Jingjing; Chen, Yang; Zhong, Ming; Tan, Ruoming (Frontiers in Pharmacology, 2024)
Background: Voriconazole is primarily metabolized by CYP2C19 and CYP3A4.Drug interactions that affect this pathway can alter its plasma exposures, resulting in untargeted voriconazole concentrations.In this case report, we described a 64-year-old man in whom continuous glucocorticoids treating non-Hodgkin's lymphoma was co-administrated with voriconazole against invasive pulmonary aspergillosis. Decrease in trough concentration (C min ) of voriconazole was found and related with coadministration of dexamethasone in this patient carrying CYP2C19 *1*2 genotype: voriconazole C min /dose ratios of 0.018 (0.1 mg L -1 /5.7 mg kg -1 day -1 ), 0.18 (1 mg L -1 /5.7mg kg -1 day -1 ), and 0.23 (2 mg L -1 /8.6mg kg -1 day -1 ) at the dexamethasone dose of 20mg, 12.5mg, and 2.5mg, respectively. Sub-therapeutic voriconazole C min was associated with high-and moderate-dose dexamethasone (20mg and 12.5mg), leading to failure of antifungal treatment.The extent of voriconazole-dexamethasone interaction was determined by the dose of dexamethasone and associated with CYP2C19 *1*2 genotype.Therapeutic drug monitoring of voriconazole is necessary to avoid clinically relevant interactions for optimal antifungal therapy.